The comparison of internalized stigmatization levels of patients with different mental disorders. (3rd May 2020) - Tanriverdi, Derya; Kaplan, Veysel; Bilgin, Sonay; Demir, Hülya
ABSTRACT: Background: Individuals with mental disorders turn to self-stigmatization in the face of stigmatization at the hands of society, and the process is internalized. Internalized stigmatization, which occurs when an individual accepts the negative stereotypes directed at him by society and, as a result, results in his withdrawal from society with negative emotions, worsens the symptoms of illness, delays recovery, and causes harm to patients. Purpose: This study was conducted to compare the internalized stigmatization levels of patients with different mental disorders. Methods: The study includes 217 patients who have been diagnosed with Schizophrenia/Schizoaffective Disorder (n:46), Substance Use Disorder (n:44), Bipolar Disorder (n: 63), Major Depression (n: 40) or any Anxiety Disorders (n: 24). The Internalized Stigma of Mental Illness (ISMI) Scale was used to collect the data. Results: The ISMI scale total score of patients was 2.59 ± 0.33. When stigmatization levels were compared by different disorders, individuals with substance use disorders suffered the highest levels of stigmatization followed by Depression, Schizophrenia/Schizoaffective disorder, Bipolar disorder and Anxiety disorder ( p < .05). Conclusions: All patients had high levels of internalized stigmatization. Individuals with substance use disorders suffered the highest levels of stigmatization. Mental health professionals should use different interventions to combat and reduce self-stigmatization among populations with different psychiatric diagnoses.